Pushing the boundaries of asteroseismic individual frequency modelling: unveiling two evolved very low-metallicity red giants - Larsen, Jens R.; Rørsted, J. L.; Aguirre Børsen-Koch, V.; Lundkvist, M. S.; Christensen-Dalsgaard, J.; Winther, M. L.; Stokholm, A.; Li, Y.; Slumstrup, D.; Kjeldsen, H.; Corsaro, E.; Benomar, O.; et al. (Astronomy and astrophysics, 2025)
Context. Metal-poor stars play a crucial role in understanding the nature and evolution of the ﬁrst stellar generation in the Galaxy. Previously, asteroseismic characterisation of red-giant stars has relied on constraints from the global asteroseismic parameters and not the full spectrum of individual oscillation modes. Using the latter, we present for the ﬁrst time the characterisation of two evolved very metal-poor stars including the detail-rich mixed-mode patterns.
Gesehen am 27.10.2025